Adaptation and Mitigation Strategy of Communities Around the Natural Tourism Area of Situ Gunung in the Era of the COVID-19 Pandemic - Anjana, Muhamad Redito Gea; Rachmawati, Eva; Soekmadi, Rinekso (Media Konservasi, 2023)
The COVID-19 pandemic has caused losses to the tourism sector and surrounding communities, including communities around the Situ Gunung natural tourism area. Adaptation and mitigation are needed to reduce the deterioration felt by the community. This research aims to analyze adaptation strategies and strategies for people in the situation of the COVID-19 pandemic. The method used is a household survey with an interview based on the method of determining samples with Isaac and Michael tables at a 10% error rate using descriptive analysis. The results showed that the quality of community adaptation is still low, adaptation strategies are carried out by people with vulnerable economic conditions based on the characteristics of their work. Tourist workers and non-tourists have different adaptation strategies but have similar mitigation strategies. Mitigation strategies are already owned by the community but are still in the initiative at the household level. In general, mitigation is planned with asset and financial management, resource allocation, finding primary and side job alternatives, and strengthening social relationships. The role of various parties, especially destination managers, is needed to strengthen adaptation and mitigation of communities at the village level to achieve resilience in the future.